THE IMPACT OF DIGITAL LITERACY IN EFL CLASSES - Najmiddinova Mumtozbegim; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Many questions are being asked about the use of mass media and technology for academic purposes. More important is how students will use the media, especially digital, for their learning. Digital literacy is becoming an increasingly effective way to learn a language and teach it to other students. From the point of view of academic goals, digital literacy is the understanding and ability to use computers or other technologies to intentionally acquire knowledge. This article will define what digital literacy is, although many other researchers have already talked about it, and its useful aspects for English language learners and teachers, as well as give some information about the best web programs for language learning. In conclusion, students should improve their language learning skills through digital literacy, and the application rates for digital literacy should also increase.